السمات الدلالية والجمالية للمسرح التجريبي الجزائري – دراسة سوسيو نصية - - بوترعة صليحة (Universty of El-oued جامعة الوادي, 2023)
الملخص: تسعى هذه الدراسة إلى مكاشفة السمات الدلالية بالموازاة مع السمات الجمالية للنص المسرحي التجريبي الجزائري وتتغيا الانتقال من المحور النصي إلى المحور الاجتماعي بتوسل المقاربة السوسيو نصية والآليات الإجرائية لمقولاتها التي جاء بها لوسيان غولدمان وبيار زيما، وتكشف هذه الدراسة عن مرحلة مفصلية من تاريخ الجزائر المعاصر وما تكبدته البلاد ابان العشرية السوداء وهو ما أعلنه النص المسرحي التجريبي الجزائري الذي توسل ظاهرة العنف وقضايا السلطة وآليات انتقالها وما عاناه المجتمع الجزائري آنذاك عبر نصين كتب أحدهما باللغة الفرنسية لصاحبة علاق بايلي، أما النص الثاني فهو النخلة و سلطان المدينة وهي مسردية للكاتب الجزائري عزالدين جلاوجي. Résumé :فرنسية أو انجلزية This study seeks to reveal the semantic features in parallel with the aesthetic features of the Algerian experimental theatrical text. It seeks to move from the textual axis to the social axis by appealing to the socio-textual approach and the procedural mechanisms of its categories that Lucien Goldman and Pierre Zema came up with. This study reveals a pivotal stage in Algeria’s contemporary history and what it has suffered. The country was during the Black Decade, which was announced by the Algerian experimental theatrical text, which addressed the phenomenon of violence, issues of power, the mechanisms of its transmission, and what Algerian society suffered at that time, through two texts, one of which was written in French by the author of Alleg Bailly, while the second text was The Palm Tree and the Sultan of the City, which is a narrative by the Algerian writer Ezzedine Djelaoudji.
أطروحة دكتوراه تخصص: نقد ومناهج في الأداب و اللغات
Keywords: المسرح التجريبي، العنف، المجتمع الجزائري، التخييل السياسي.; Experimental theatre; violence; Algerian society; political imagination